ANALISIS PENYEBAB TERJADINYA PEYALAHGUNAAN DATA PRIBADI YANG DIGUNAKAN UNTUK MELAKUKAN PINJAMAN ONLINE DI KOTA PONTIANAK DI TINJAU DARI ASPEK KRIMINOLOGI - NIM. A1011161104, YESSI FITRIANI (Fakultas Hukum Universitas Tanjungpura, 2023)
AbstractCriminology is needed to solve personal problems that cannot be resolved solely by relying on norms in general criminal law. Likewise, in reviewing the criminal act of sending other people's personal data which is used to register for online loans on Traveloka paylater which is currently rampant, it violates the development of information and transactions online or electronically. It is necessary to understand criminology to see the factors and methods of the perpetrator in protecting other people's personal data which is used to register for online loans. Based on this, criminology is also very useful for seeing and finding out the consequences of a crime committed by someone, such as cybercrime which is related to the accumulation of other people's personal data which is used to register for online loans. This can be said to be quite a crime. serious, so it requires appropriate handling to prevent cybercrime related to brokering other people's personal data, considering the potential for this crime to occur is very large, coupled with system weaknesses on the internet which make it easy for cybercrime to occur.The formulation of the problem in this research is